Evaluación de las aguas del Itaya, tramo puente Itaya - centro poblado "12 de Octubre", Iquitos, 2018 - Noriega Arévalo, Daniel Joa (2022)
In the present study "EVALUATION OF THE WATERS OF THE ITAYA, SECTION: ITAYA BRIDGE-POPULATED CENTER "12 DE OCTUBRE", IQUITOS, 2018." Developed at the National University of the Peruvian Amazon, it is intended to determine the conditions in which the water resource, so important for the life and health of human beings, from the Itaya River is being used in the different domestic activities by the accentuated populations in the area. The project is framed in the type of descriptive, qualitative research, since it describes and determines the properties, characteristics of the body of water and the parametric phenomena that are subjected to analysis. Three samplings were carried out, one during the dry season, the dry season and the growing season at three different points in the area with the aim of making a qualitative study of the quality conditions in which they are found, determining the points of greatest risk for the population that He uses it. In the analyzes carried out in the Chemical Analysis Laboratory of the UNAP, EPS SEDALORETO quality control laboratory and in the quality control laboratory facilities of AJEPER Peru-Iquitos, relatively significant results were obtained, as is the case of the pH that resulted slightly acid, of 5.75 however, in turbidity and color high values of 35.43, 30.8 UNT and 15.0,12.70 UCV pt/co are observed, some very low dissolved Oxygen values, 2.10, 1.30 mg/L in the case of metals heavy we have results that are within the maximum permissible limits, the most outstanding results are the total coliforms 120.0, 113.30 NMP and thermotolerant that are very high 24.70, 22.70 NMP and that produces greater concern for which greater attention should be paid to this problem to avoid consequences that can lead to health problems.